Pengaruh Pupuk Majemuk Tablet pada Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Anggeraini, Rinanda; Utoyo, Bambang; Indrawati, Wiwik (Jurnal Agro Industri Perkebunan, 2017)
Cocoa (Theobroma cacao L.) is one of the estate crop commodities that is currently being developed because the cocoa plant is one of the export commodities that produce a lot of foreign exchange and has a role as high value sector besides oil and gas. Cocoa farming can increase the income of cocoa farmers, create and expand employment. This experiment used Randomized Block Design (RBD) which consisted of 4 treatments that was repeated 6 times (control, 1 tablet.polybag-1, 2 tablet.polybag-1, 3 tablet.polybag-1). This study was conducted to determine the best rate of compound fertilizer tablets for cocoa seedlings growth. The data obtained were analyzed by analysis of variance at 95% accuracy level. The results showed that there was a compound effect on the growth of cocoa seedlings to the variable of seed height, stem diameter, leaf number, leaf area, dry root weight, and total dry weight of stalk. Application of tablet compound fertilizer 1 tablet.polybag-1 gives the best results on the growth of cocoa seedlings.     Keywords: cocoa seedlings growth, inorganic fertilizer, tablet compound fertilizerPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/647